Brassica oleracea L. var. botrytis L. CGN11098 ... - GLIS Of The ITPGRFA (Centre for Genetic Resources, the Netherlands, 2017)
Plant Genetic Resource. Taxonomy: Brassica oleracea L. var. botrytis L. Common name(s): cruciferae, Crucifers Other names: White Fox Conserved by: Centre for Genetic Resources, the Netherlands (CGN), Netherlands (Kingdom of the) Local sample unique identifier: CGN11098 Method of creation: Acquisition Date: 1989-10-13 Historical: No Biological status: Advanced or improved cultivar MLS status: Included ...